Long noncoding RNA n339260 promotes vasculogenic mimicry and cancer stem cell development in hepatocellular carcinoma. Issue 10 (14th August 2018) - Zhao, Xiulan; Sun, Baocun; Liu, Tieju; Shao, Bing; Sun, Ran; Zhu, Dongwang; Zhang, Yanhui; Gu, Qiang; Dong, Xueyi; Liu, Fang; Zhao, Nan; Zhang, Danfang; et al.
Abstract : Vasculogenic mimicry (VM) refers to the unique capability of aggressive tumor cells to mimic the pattern of embryonic vasculogenic networks. Cancer stem cells (CSC) represent a subpopulation of tumor cells endowed with the capacity for self‐renewal and multilineage differentiation. Previous studies have indicated that CSC may participate in the formation of VM. With the advance of high‐resolution microarrays and massively parallel sequencing technology, long noncoding RNAs (lncRNAs) are suggested to play a critical role in tumorigenesis and, in particular, the development of human hepatocellular carcinoma (HCC). Currently, no definitive relationship between lncRNA and VM formation has been described. In the current study, we demonstrated that expression of the lncRNA, n339260, is associated with CSC phenotype in HCC, and n339260 level correlated with VM, metastasis, and shorter survival time in an animal model. Overexpression of n339260 in HepG2 cells was associated with a significant increase in CSC. Additionally, the appearance of VM and vascular endothelial (VE)‐cadherin, a molecular marker of VM, was also induced by n339260 overexpression. Using a short hairpin RNA approach, n339260 was silenced in tumor cells, and knockdown of n339260 was associated with reduced VM and CSC. The results of this study indicate that n339260 promotes VM, possibly by the development of CSC. The related molecular pathways may be used as novel therapeutic targets for the inhibition of HCC angiogenesis and metastasis. Abstract : Overexpression of long noncoding RNA n339260 in HepG2 cells was associated with cancer stem cells (CSC) phenotype development. Additionally, the appearance of vasculogenic mimicry (VM) and vascular endothelial (VE)‐cadherin expression, a molecular marker of VM, was also induced by n339260 overexpression. The results of this study demonstrate that n339260 promotes VM, possibly by the development of CSC.